Synthesis, characterization and antioxidant activity of 3-(2-Amino-1,3-Selenazol-4-yl)-2H-Chromen-2-Ones derivatives - Nurul Zawani Alias; Nurul Izzaty Hassan; Zaini Yusoff; Sharizal Hasan; Wan Yaacob Wan Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2018)
Selenocompounds have been widely synthesized for their potential in pharmacology. Ebselen, a selenazole oxide, is a glutathione peroxidase mimic which is known to possess high antioxidant activity. Four derivatives of 3-(2-amino-1,3- selenazol-4-yl)-2H-chromen-2-ones were synthesized by reacting 3-(2-bromoacetyl)-chromen-2-one derivatives with selenourea through Hantzsch reaction using NaF as a catalyst in methanol-water (1:1) at room temperature. These reactions were completed in 30 min and purified using column chromatography eluted with n-hexane-ethyl acetate (7:3) to give 50-83% yields. All the compounds were successfully characterized using IR, 1H and 13C NMR as well as mass spectrometry. The synthesized compounds were tested with DPPH assay to determine the free radical scavenging activity and were compared to gallic and ascorbic acids as standard. Nonetheless, all compounds exhibited weak free radical scavenging activity with IC50 value ranging from 672.13 to 984.03 μM signifying that the derivatives may possess weak antioxidant activities.